Analysis and assessment of smart grid: a review. (2018) - Khare, Vikas; Khare, Cheshta J.; Nema, Savita; Baredar, Prashant
Smart grid mainly based on different class of technology such as computer-based remote control and automation of power or energy grid and in another way, it would be a path in which transmission and distribution are controlled by computer and information technology-based system. Smart grid is a recognised perception being rapidly introduced in the power industry and it plays a key role in the development of the worldwide power sector. This paper presents a review of analysis and assessment of the smart grid on the basis of architectural design, communication, measurement technology, assessment of smart grid by optimisation technique, reliability, economic assessment, asset management, cyber physical security, game theoretic assessment of smart grid, sustainable energy option and control system of smart grid.